Kinerja Petugas Rekam Medis di Rumah Sakit Bhakti Mulia Tahun 2019 - Siva Maulia Fauziah; Nanda Aula Rumana; Deasy Rosmala Dewi; Laela Indawati (Lembaga Penerbitan Universitas Esa Unggul, 2020)
AbstractMedical records are important units in hospitals; therefore, the organization of medical records must be managed by personnel who are competent in their fields. The purpose of this research is to know the description of the characteristics and performance of officers.The research method uses descriptive quantitative analysis, the number of respondents was 26 officers. The results of the study, obtained by officers in the medical record unit who came behind medical record education (35%), the last education was SMA/SMK (50%), never attended training (75%), the average length of service of the officer was 38 months, average age of officers 24 years, gender of female officers (63%), high knowledge (100%). In the case mix unit, there were officers who did not graduate from medical records (44.4%), the last education was a diploma (44.4%), never attended training (88.9%), the average length of work 24 months a month, the sex of female officers (100%), average age of staff 24 years, high knowledge (100%). In the TPP unit, officers who have not graduated from medical records (100%), the last education of officers are SMA / SMK (100%), never attended training (100%), the average length of service of officers is 18 months, the sex of female officers (100%), high knowledge (55.6%). The average performance of officers in the medical record unit (55.41%), case mix (56.29%), and TPP (55.18%). It is recommended to Bhakti Mulia Hospital to provide education or training to officers on medical record knowledge, officers can manage time so that they can complete work on time.Keyword: characteristic, performance, medical record officers.AbstrakRekam medis adalah unit penting di rumah sakit, oleh karena itu penyelenggaraan rekam medis harus dikelola oleh personil-personil yang kompeten dibidangnya. Tujuan dalam penelitian ini adalah mengetahui gambaran karakteristik dan kinerja petugas. Metode penelitian menggunakan analisis kuantitatif deskriptif, jumlah responden sebanyak 26 petugas. Hasil penelitian, didapat petugas di unit rekam medis yang berlatang belakang pendidikan rekam medis (35%), pendidikan terakhir adalah SMA/SMK (50%), tidak pernah mengikuti pelatihan (75%), rata-rata lama bekerja petugas adalah 38 bulan, rata-rata usia petugas 24tahun, jenis kelamin petugas perempuan (63%), pengetahuan tinggi (100%). Pada unit casemix terdapat petugas bukan lulusan rekam medis(44,4%), pendidikan terakhir adalah diploma (44,4%), tidak pernah mengikuti pelatihan(88,9%), rata-rata lama bekerja petugas 24 bulan, jenis kelamin petugas perempuan(100%), rata-rata usia petugas 24 tahun, pengetahuan tinggi(100%). Di unit TPP petugas yang bukan lulusan rekam medis (100%), pendidikan terakhir petugas adalah SMA/SMK (100%), tidak pernah mengikuti pelatihan(100%), rata-rata lama bekerja petugas adalah 18 bulan, jenis kelamin petugas perempuan (100%), pengetahuan tinggi(55,6%). Rata-rata kinerja petugas di unit rekam medis (55,41%), casemix (56,29%), dan TPP (55,18%). Disarankan kepada Rumah Sakit Bhakti Mulia agar memberikan edukasi atau pelatihan kepada petugas tentang pengetahuan rekam medis, petugas dapat memanajemen waktu agar dapat menyelesaikan pekerjaan tepat waktu.Kata Kunci: karakteristik, kinerja, petugas rekam medis.